الخصائص السيكومترية لاستبانة تصورات الطلبة حول التقييم الإلكتروني - الخروصي, حسين; الوهيبي, إبراهيم (جامعة الوادي - University of Eloued, 2021)
الملخص: هدفت الدراسة إلى التحقق من الخصائص السيكومترية لاستبانة تصورات الطلبة حول التقييم الإلكتروني، وتم استخدام المنهج الوصفي، وتكونت عينة الدراسة من (402) طالباً وطالبة من طلبة جامعة السلطان قابوس، وتم التحقق من الصدق الظاهري لفقرات الاستبانة (13 فقرة)، وتوصلت نتائج التحليل العاملي الاستكشافي إلى أن الفقرات تشبعت على عامل واحد فقط بلغت قيمة جذره الكامن (7.54) مفسراً نسبة مقدارها (58.01%) من التباين الكلي للفقرات، وتم إيجاد صدق الاتساق الداخلي للفقرات، وتراوحت قيم معاملات ارتباط درجة كل فقرة مع الدرجة الكلية ما بين (0.55-0.83)، وجميعها دالة إحصائياً، أما نتائج التحليل العاملي التوكيدي فقد توصلت إلى استقرار البنية الكامنة للاستبانة، مما يشير إلى تمتع الأداة بمستوى مقبول من صدق البناء، وبلغ معامل ألفا لكرونباخ (0.93) وبلغ معامل ثبات الاستقرار (0.94)، مما يؤكد تمتع درجات الاستبانة بدلالات ثبات مقبولة. في ضوء هذه الدلالات نستنتج أن الاستبانة تتمتع بخصائص سيكومترية جيدة تجعلها أداة موثوقة يمكن استخدامها للتعرف على آراء الطلبة بشأن عملية التقييم الالكتروني في المقررات الدراسية. Abstract: The study aimed to verify the psychometric properties of the Questionnaire of Students' Perceptions about Electronic Assessment. The descriptive research methodology was used. The study sample consisted of (402) students from Sultan Qaboos University. The face validity of the questionnaire's items (13 items) was established. The results of the exploratory factor analysis showed that the items of the questionnaire loaded on one factor only (eigenvalue = 7.54) explaining (58.01%) of the total variance of the items. The internal consistency of the items was also validated through statistically significant correlation coefficients between item score and total score ranging between (0.55 – 0.83). Results of the confirmatory factor analysis showed the stability of the underlying structure of the Questionnaire of Students' Perceptions about Electronic Assessment, which indicates that the questionnaire has an acceptable level of construct validity. The Cronbach alpha coefficient was (0.93) while the stability coefficient was (0.94), which confirms that the questionnaire’ scores have acceptable levels of reliability. In light of the indications of validity and reliability, it can be concluded that the questionnaire has good psychometric properties that make it a reliable tool that can be used to identify students' opinions about the electronic assessment process in the curricula.
مقال
Keywords: تقييم الكتروني ; خصائص سيكومترية ; صدق ; ثبات ; تصورات الطلبة; electronic assessment; psychometric properties; validity, reliability; students’ perceptions